Discussion of four species of Anomala Samouelle from Mêdog, Xizang and description of one new species of Melanopopillia Lin from Guangxi, China (Coleoptera: Scarabaeidae: Rutelinae) - Lu, Yuan-Yuan; Borjigin, Mende; Bai, Ming (Zootaxa, 2026)
Four species comprising the so-called Anomala cinderella species-group are herein treated based on material recently collected from Mêdog and the contiguous Himalayan region. Members of this assemblage, including Anomala cinderella Arrow, 1917, A. liuhaoyii Zhao, 2025, A. pemako Zhao, 2025, and A. piliscutella Lin, 1981, are characterized by a distinctively testaceous to rufescent habitus and a pronotum densely clothed in elongate, yellowish setae. The present contribution provides a key to these species, detailed descriptions, differential diagnoses and distribution for each taxon. Furthermore, Melanopopillia guangxiensis sp. nov. is described from Guangxi Zhuang Autonomous Region.